(untitled) (Mustansiria Dental Journal, 2018)
Background: Bone morphogenetic proteins (BMPs) are secretory signal molecules which have a variety of regulatory functions during morphogenesis and cell differentiation. Teeth are typical examples of vertebrate organs in which development is controlled by sequential and reciprocal signaling between the epithelium and mesenchyme. In addition, tooth development is characterized by formation of mineralized tissues, dentin and cementum as well as epithelially derived enamel. BMp 7 plays a role with other signaling molecules in tooth development. Aim of the study: To perform immune-histochemical analysis of the expression of BMP7starting from initiation of tooth development to completion of crown morphogenesis when dentine and enamel matrices are being deposited in rat incisor tooth Materials and Methods: Sixteen rat embryos were obtained from pregnant rats in gestation periods 16th,17th,18th,20th intrauterine life and eight neonatal one day and 3 day old rat were included in this study . Each period involved 4 embryos or neonatal rats. Premaxilla ( containing incisor teeth) was dissected and fixed in 10% buffered formalin and embedded in paraffin. Block sections (4 μm thickness) for Immunohistochemical localization of BMP7. Results: Positive expression of BMP7 was recorded in ectoderm derived cells only, in developing tooth germ include oral epithelia, dental lamina and inner enamel epithelia in gestation period 16th,17thand 18thintrauterin life of rat embryo. Then the expression was illustrated in specialized cell of dental papilla the odontoblast and the developing dentin matrix .Ameloblast cell expressed too BMP7 in its formative and maturative stages. Conclusion: Bone morphogenetic protein 7 may play key roles in mediating induction, differentiation events during tooth development.